ASURANSI JIWA DAN PEMBAYARAN SANTUNAN - Sri Retno Widyorini (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2020)
PT Asuransi Jasa Raharja is a state-owned company engaged in insurance, which is included in the social insurance group. Provisions regarding the provision of compensation and compensation are regulated in Law Number 33 of 1964 concerning Obligations for Passenger Accident Compulsory Funds, the Implementation Regulations are set out in PP Number 17 of 1965. The public tends not to know about the conditions for submitting compensation payment claims, i.e. by filling out the questionnaire form. A form for obtaining financial support is provided by PT. Jasa Raharja Insurance, which contains: 1 information on the identity of the victim / heir, filled in who submitted compensation funds, 2) information on the traffic accident filled and authorized by the police, 3) information on the health / condition of the victim, filled by the hospital / doctor who treated victim, 4). If the victim dies about the validity of the heirs filled in by government employees / lurah / camat PT Asuransi Jasa Raharja will examine all the requirements and then process them, if the residence of the victim / heir is the same as the area where the accident occur and also the working area of the PT Asuransi Jasa Raharja branch then the request for insurance compensation will be served and completed at the same time by the relevant branch office, but vice versa if the place / area where the accident occurred is different from the working area of PT Asuransi Jasa Raharja, the request for rights to compensation can be submitted to the branch office ter close.